Literasi Media Digital Sebagai Upaya Meningkatkan Kompetensi Penulisan Berita - Aliasan Aliasan; Amin Sihabuddin; Neni Noviza; Manah Rasmanah (Wardah, 2022)
Abstract : The development of technology makes the news continue to grow so that we can easily find news. However, in producing news that is in accordance with the rules, competency is needed in writing. This study discusses the use of digital media literacy in an effort to increase the competence of writing news for journalism students. This study aims to determine the relationship between digital media literacy and news writing skills. The method in this study uses a mix method approach, a quantitative approach is used to determine the level of understanding and relationship between variables. Meanwhile, qualitative research is used to look at the factors that influence news writing. This research was conducted at the Faculty of Da'wah and Communication. The study population consisted of 240 students with a sample of 118 students who were taken using a purposive random sampling technique. Quantitative instruments use media literacy questionnaires and news writing, qualitative instruments use interviews. Quantitative data analysis techniques using simple linear regression and qualitative using data presentation, data reduction. The results showed that the level of digital media literacy of students was in the medium category while the understanding of news writing was in the moderate category of 59%. thus there is a significant relationship between digital media literacy variables and news writing competence. Keywords: digital media literacy, competence, news writing